Catheter-related infections with emphasis on pathogenesis and diagnosis - De Souza da Cunha, Maria de Lourdes Ribeiro [UNESP] (My University, 2011)
Catheter-related infections (CRI) are one example of this reality and occur when a microorganism invades the bloodstream through a vascular catheter. Infections associated with the use of intravascular devices account for 10 to 20% of all nosocomial infections and are one of the most frequent causes of morbidity and mortality, representing a source of bacteremia and sepsis in hospitalized patients and increasing the length of hospital stay, hospitalization costs and mortality. Approximately 65% of these infections result from the migration of microorganisms of the skin microbiota from the insertion site of the catheter. Intraluminal contamination is observed in 30% of cases and 5% occur through other routes such as infusion of contaminated fluids and distant infectious foci. All of these contamination sources are important, but the most prevalent is contamination with microorganisms of the patient himself in areas close to the insertion site of the catheter. This explains why coagulase-negative staphylococci (CNS) are the microorganisms most frequently associated with this type of infection since they are also the most common in skin. CRI are diagnosed when identical microorganisms are isolated from catheter cultures and from blood cultures in the absence of any apparent source of infection, except for the catheter. The reliability of catheter cultures for the diagnosis of CRI depends on the culture technique used. The objective of this review was to discuss various aspects of CRI such as diagnosis, incidence, etiology, pathogenesis and new prevention strategies based on the knowledge of the mechanisms of bacterial adhesion and biofilm formation. Biofilm formation is regulated by the exchange of chemical signals between cells during a process called 'quorum-sensing'. A new approach to prevent the colonization of catheters and to reduce infections related to these devices is to interfere with this cell-cell communication which permits these microorganisms to organize themselves into complex biofilms, protecting them from the host immune system and conferring greater resistance to antimicrobials.